ANALISIS YURIDIS TERHADAP WANPRESTASI DALAM PERJANJIAN BORONGAN PEKERJAAN DIBIDANG JASA BACA METER ANTARA PT. PLN (PERSERO) CABANG SIGLI DENGAN PT. MULTI GUNA PUTRA ACEH MANDIRI - ELVIRA ROSALLY OKTAVIANI (PREMISE LAW JURNAL, 2016)
The research problems are how about the process of the implementation of contracted work contract in recording electric meter between PT. PLN (PERSERO) Sigli branch, and PT. Multi Guna Putra Aceh Mandiri and how about the settlement and the liability of the party that breaches the contract (default). The research used judicial normative and descriptive analytic methods which described, analyzed, and explained the legal provisions in theory and practice obtained from field study. The result of the research showed that PT. PLN (PERSERO) has breached the contract (default) to PT. Multi Guna Putra Aceh Mandiri because up to now PT. PLN (PERSERO) Sigli branch has not paid off the fee to PT. Multi Guna Putra Aceh Mandiri although the contracted work in recording electric meter is in accordance with the contract signed by both parties. Keywords: Contract in Recording Electric Meter